Optimal Methods for the Management of Iatrogenic Colonoscopic Perforation - Dae Kyu Shin; Sun Young Shin; Chi Young Park; Sun Mi Jin; Yang Hyun Cho; Won Hee Kim; Chang-Il Kwon; Kwang Hyun Ko; Ki Baik Hahm; Pil Won Park; Jong Woo Kim; Sung Pyo Hong (Korean Society of Gastrointestinal Endoscopy, 2016)
Background/Aims: Colonoscopic perforations have been managed with exploratory laparotomy, and have resulted in some morbidity and mortality. Recently, laparoscopic surgery is commonly performed for this purpose. The aim of this study was to compare the outcomes of several management strategies for iatrogenic colonoscopic perforations. Methods: We retrospectively reviewed the medical records of patients who had been treated for colonoscopic perforation between January 2004 and April 2013 at CHA Bundang Medical Center in Korea. Results: A total of 41 patients with colonoscopic perforation were enrolled. Twenty patients underwent conservative management with a success rate of 90%. Surgical management was performed in 23 patients including two patients who were converted to surgical management after the failure of the initial conservative management. Among 14 patients who underwent surgery at 8 hours after the perforation, there was no considerable difference in adverse outcomes between the laparotomy group and the laparoscopic surgery group. The medical costs and claim rate were 1.45 and 1.87 times greater in the exploratory laparotomy group, respectively. Conclusions: Conservative management of colonoscopic perforation could be an option for patients without overt symptoms of peritonitis or with a small defect size. If surgical management is required, laparoscopic surgery may be considered as the initial procedure even with a delayed diagnosis.